MultiPole pacing in non‐responders to cardiac resynchronization therapy: Results from the QP ExCELs/MPP sub‐study. Issue 10 (9th September 2021) - Drucker, Michael N.; Manyam, Harish; Singh, Gurjit; Glascock, Dennis N.; Gillett, Shane; Miller, Crystal; Sharmin, Kazi; Parks, Kimberly A.
Abstract: Background: Multisite LV stimulation therapy allows for stimulation of two different left ventricular pacing vectors within a single LV lead and may improve responsiveness to cardiac resynchronization therapy (CRT). This study prospectively evaluated the safety and efficacy of the MultiPole Pacing (MPP) feature in CRT non‐responder patients. Methods and Results: CRT non‐responders with a standard CRT‐D indication were eligible for enrollment into the MPP Sub‐Study. Patient status, NYHA classification, Patient Global Assessment (PGA), and adverse events were collected at follow‐up. A clinical composite score (CCS) was determined at the 6 month follow‐up visit. The primary objective was defined as the proportion of patients with an improved CCS. Safety was evaluated as freedom from MPP system related adverse events requiring additional invasive intervention to resolve. A total of 53 patients were enrolled across 26 U.S. centers. The cumulative follow‐up duration was 24.1 years. CCS was improved in 35.6% of patients ( p  < .0001 when compared to a performance goal of 3%) after 6 months of MPP therapy. When incorporating patient feedback into a modified CCS, 60.0% of patients showed an improvement. Three patients (5.7%) experienced hospitalization for heart failure, and three patient deaths occurred over the follow‐up period. No MPP system‐related events were reported for an AE‐free rate of 100% (95% CI 93.28% to 100.0%). Conclusions: The results of this small, non‐randomized study suggest that the MPP feature is safe, and may be effective at converting a percentage of CRT non‐responders to responders. Larger, randomized studies are needed to confirm this result.